Spatial phase distributions in solution-based and evaporated Cs-Pb-Br thin films - Caicedo Dávila, Sebastián; Funk, Hannah; Lovrinčić, Robert; Müller, Christian; Sendner, Michael; Cojocaru-Mirédin, Oana; Lehmann, Frederike; Gunder, René; Franz, Alexandra; Levcenco, Sergej; Cohen, Ayala V.; Kronik, Leeor; et al. (The journal of physical chemistry. C, Energy, materials, and catalysis, 2019)
In recent years, inorganic cesium−lead−halide perovskites, CsPbX3 (X = I, Br, Cl), have attracted interest for optoelectronic applications such as highly eﬃcient thin-ﬁlm light-emitting diodes or wide-gap absorber materials for photovoltaics. However, phase segregation and secondary phases in as-deposited thin ﬁlms are still considered to be limiting factors for devices based on CsPbX3. Here, we report a correlative electron microscopy and spectroscopy approach for the identiﬁcation of secondary phases and their distributions in Cs−Pb−Br thin ﬁlms, deposited by solutionbased and coevaporation methods on various substrates. We identiﬁed phases by their compositional, structural, and optoelectronic properties, using X-ray diﬀraction, spectroscopy, and a variety of microscopy techniques. We found that the Cs−Pb−Br ﬁlms contain ternary Cs4PbBr6 and CsPb2Br5 phases in addition to CsPbBr3, a ﬁnding consistent with calculations of formation enthalpies by means of the density functional theory showing that these values are very similar for the three ternary phases. We ﬁnd that these phases can exhibit diﬀerent spatial distributions inside the ﬁlm and discuss the inﬂuence of the deposition method and synthesis parameters on the resulting phase composition of the Cs−Pb−Br layers.
Gesehen am 02.03.2021